Comparison between the clinical symptoms of peripheral neuropathy inflammation and nervous planning results in (type II) diabetes patients - Majid Neamah Al-Akayeshi, Israa; Jwad Al-Jammali, Saher Mahmood; Hamad Al-Shimmari, Ammar Jabbar (Al-Qadisiyah Journal of Pure Science, 2018)
Diabetes mellitus is one of the most chronic diseases that is widely spread all over the world and affects all age groups. The disease has a vast potential to affect almost every body organ, especial the peripheral nerves, which causes high mortality rates from disease complications. These complications cause damage in the organs of the body including the nerves located in the limbs that generate an intense heat resulting from the destruction of nerve fibers in addition to the acute pain resulting from the effect of diabetes in those nerves. This study was designed to determine the sensitivity of those nerves by displaying the results of nerve conduction study for patients and compared it with their clinical examination to determine the severity of numbness and assess the level of pain in the upper and lower limbs. The study was carried out at the Diabetes and Endocrinology Center in Al-Sader Medical City in Al- Najaf governorate and it included following up the case of (78) patients with diabetic peripheral neuropathy, (32) men and(46)women their ages ranging between(35-68) year and they were divided into three age groups ,the study was began from 5/9/2014 until 7/4/2015. The study excluded the patients with peripheral neuropathy but have foot ulceration because the nerve conduct system (SUDOSCAN REPORT) was used in the current study, cannot perform nerve conduction study for patients with foot ulceration also smokers and the patients who taking treatment for diabetic peripheral neuropathy. During this study the clinical examination for patients was performed and compared with the nerve conduction results of them , also all the information related with the history of patients were recorded . The present study has shown a significant difference (P <0.05) between the clinical tests of the patients who were tested by tuning fork as while as nerves needle test and between nerve conduction study for both sexes were included in the study. The results of the study did not show any significant difference(P>0.05) when compared the results of nerve conduction study among the different age groups for males. For females however, there was a significant difference (P<0.05) among the different age groups. When compared the glycosylated hemoglobin (HbA1c) levels over the past three months, there were no significant differences (P>0.05) for males and females . The results of the current study did not reveal a significant difference (P>0.05) between the body mass index among males, but it noticed a significant difference (P<0.05) among females with peripheral diabetic neuropathy.